PERANAN KELOMPOK USAHA BERSAMA DALAM PERBAIKAN POSISI TAWAR DAN PENDAPATAN PERAJIN GULA KELAPA DI KABUPATEN BANYUMAS THE ROLE OF COOPERATIVE BUSINESS GROUP IN IMPROVING INCOME AND BARGAIN POSITION OF COCONUT SUGAR INDUSTRY AT BANYUMAS REGENCY - Purwaningsih, Ari; Sriningsih, Endang; Rosyad, Anisur (Pembangunan Pedesaan, 2005)
Research aimed at expressing the real role of Cooperative Business Group (CBG) institution in improving position of coconut sugar industry at selling price and income aspects. The research was carried out at Banyumas Regency using survey method with stratified random sampling. Numbers of sample were 40 industries consisted of member and non-member of the CBG. Data were analyzed by impairment comparison test analysis. Result of the research showed that the CBG had a role in improving farmer bargain position through the sold sugar price. Average of the price obtained by the CBG members was greater than the CBG nonmember. The income of sold price was higher at the members caused by the produced sugar quality. The research expressed the significant different income of the CBG members compared to the CBG non-member too.